2008
DOI: 10.1098/rstb.2008.2261
|View full text |Cite
|
Sign up to set email alerts
|

Pluripotency and nuclear reprogramming

Abstract: Embryonic stem cells are promising donor cell sources for cell transplantation therapy, which may in the future be used to treat various diseases and injuries. However, as is the case for organ transplantation, immune rejection after transplantation is a potential problem with this type of therapy. Moreover, the use of human embryos presents serious ethical difficulties. These issues may be overcome if pluripotent stem cells are generated from patients' somatic cells. Here, we review the molecular mechanisms u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
80
0
6

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(87 citation statements)
references
References 123 publications
(137 reference statements)
1
80
0
6
Order By: Relevance
“…4C). These results are consistent with the occurrence of epigenetic remodeling during reprogramming by gene transduction (Yamanaka, 2008;Wang and Na, 2011). In addition, chromosomal G-banding analysis indicated that C1-OSN hiPSCs had a normal (46, XY) karyotype (Fig.…”
Section: Resultssupporting
confidence: 86%
“…4C). These results are consistent with the occurrence of epigenetic remodeling during reprogramming by gene transduction (Yamanaka, 2008;Wang and Na, 2011). In addition, chromosomal G-banding analysis indicated that C1-OSN hiPSCs had a normal (46, XY) karyotype (Fig.…”
Section: Resultssupporting
confidence: 86%
“…Molecularly undefined reprogramming methods, such as SCNT, fusion of somatic cells with ES cells, or explantation of cells in tissue culture, use a milieu of components or elements that are largely unknown to achieve cellular reprogramming ( Fig. 1) (Hochedlinger and Jaenisch 2006;Rodolfa and Eggan 2006;Yamanaka 2008). For instance, in SCNT, undefined factors present in the oocyte cytoplasm reprogram the injected nucleus to pluripotency (e.g., transcription factors, histone-modifying and chromatin-remodeling enzymes, and DNA demethylases).…”
Section: Defining Cellular Reprogrammingmentioning
confidence: 99%
“…Such global changes in chromatin structure are presumed to be important for cell commitment by stabilizing gene expression programs. Committed somatic cells can be reprogrammed back to the pluripotent ESC state by forced expression of a specific set of transcription factors to create induced pluripotent stem cells (iPSCs) (4,5). However, some genes are difficult to reprogram, resulting in the generation of partially reprogrammed (p)iPSCs (6,7).…”
mentioning
confidence: 99%